61 Psychosocial correlates of physical violence perpetration and sexual coercion among at-risk emerging adults. (19th September 2017) - Ramirez, Jessica; Stein, Sara; Zbizek-Nulph, Lisa; Cunningham, Rebecca; Walton, Maureen; Ngo, Quyen
Abstract : Purpose: Violence is the second leading cause of death among youth. Alcohol misuse and psychopathology have consistently been linked with violence perpetration. This study examines the relationship between alcohol misuse, reporting a mental health concern, trait mindfulness and dating violence perpetration (physical perpetration [PDV] and sexual coercion [SDV]). Methods: Emerging adults (EA; 18–25 years old) were recruited from an urban emergency department (ED) and completed a self-administered computer survey that asked about DV, alcohol use, mental health (anxiety and depression), trait mindfulness, and demographics. Two negative binominal logistic regressions were conducted separately for PDV and SDV, examining associations with alcohol use, drug use, trait mindfulness, anxiety, depression, and demographic characteristics. Results: The sample included 665 EAs (68.5% Male; 61.2% Black, 39% White/other). Analyses showed that identifying as Black was associated with PDV compared to identification as White/other. Analyses also showed that alcohol misuse and anxiety were positively associated with PDV, such that higher levels of alcohol misuse and anxiety predicted to PDV. Lower levels of trait mindfulness were significantly associated PDV. The second analysis revealed that identifying as Black was associated with SDV compared to identification as White/other. Being male was significantly correlated with SDV compared being female. Receiving public assistance was also positively associated with SDV and trait mindfulness was negatively associated with SDV. Post-hoc analyses were conducted to examine interactions between mental health, substance use and trait mindfulness. Conclusions: Findings indicate different contributing factors among those who perpetrate PDV and SDV. One factor that is consistent in both PDV and SDV is lower levels of trait mindfulness and should be a focus of psychotherapeutic interventions to reduce PDV and SDV. Contributions: These findings warrant development of future interventions and public policies geared toward supporting preventative measures to decrease PDV and SDV.